2022
DOI: 10.1055/a-1922-7646
|View full text |Cite
|
Sign up to set email alerts
|

Post-EMR for colorectal polyps, thermal ablation of defects reduces adenoma recurrence: A meta-analysis

Abstract: Introduction Adenoma recurrence is one of the key limitations of EMR which occur in 15% to 30% in first surveillance colonoscopy. The main hypothesis behind adenoma recurrence is due to left over micro-adenomas at the margins of post EMR defects. In this systematic review and meta-analysis, we evaluate the efficacy of snare tip soft coagulation (STSC) at the margins of mucosal defects to reduce adenoma recurrence and bleeding complications. Methods Electronic databases such as PubMed and the Cochrane library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…A recent multicenter three-arm randomized controlled trial (RCT) on 384 patients by Rex et al, comparing APC, STSC, and placebo, found superiority of thermal ablation compared to placebo [ 16 ]. Prior systematic reviews and meta-analyses have shown the efficacy and safety of thermal ablation modalities [ 18 , 19 , 20 ]. However, no updated network meta-analysis incorporating an RCT has been performed to draw comparison between these three modalities.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter three-arm randomized controlled trial (RCT) on 384 patients by Rex et al, comparing APC, STSC, and placebo, found superiority of thermal ablation compared to placebo [ 16 ]. Prior systematic reviews and meta-analyses have shown the efficacy and safety of thermal ablation modalities [ 18 , 19 , 20 ]. However, no updated network meta-analysis incorporating an RCT has been performed to draw comparison between these three modalities.…”
Section: Introductionmentioning
confidence: 99%